Sole rearrangement but not amplification of MYC is associated with a poor prognosis in patients with diffuse large B cell lymphoma and B cell lymphoma unclassifiable. (29th July 2016) - Landsburg, Daniel J.; Falkiewicz, Marissa K.; Petrich, Adam M.; Chu, Benjamin A.; Behdad, Amir; Li, Shaoying; Medeiros, L. Jeffrey; Cassaday, Ryan D.; Reddy, Nishitha M.; Bast, Martin A.; Vose, Julie M.; Kruczek, Kimberly R.; et al.
Summary: Rearrangement of MYC is associated with a poor prognosis in patients with diffuse large B cell lymphoma (DLBCL) and B cell lymphoma unclassifiable (BCLU), particularly in the setting of double hit lymphoma (DHL). However, little is known about outcomes of patients who demonstrate MYC rearrangement without evidence of BCL2 or BCL6 rearrangement (single hit) or amplification (>4 copies) of MYC . We identified 87 patients with single hit lymphoma (SHL), 22 patients with MYC ‐amplified lymphoma (MYC amp) as well as 127 DLBCL patients without MYC rearrangement or amplification (MYC normal) and 45 patients with DHL, all treated with either R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) or intensive induction therapy. For SHL and MYC amp patients, the 2‐year progression‐free survival rate (PFS) was 49% and 48% and 2‐year overall survival rate (OS) was 59% and 71%, respectively. SHL patients receiving intensive induction experienced higher 2‐year PFS (59% vs. 23%, P  = 0·006) but similar 2‐year OS as compared with SHL patients receiving R‐CHOP. SHL DLBCL patients treated with R‐CHOP, but not intensive induction, experienced significantly lower 2‐year PFS and OS ( P  < 0·001 for both) when compared with MYC normal patients. SHL patients appear to have a poor prognosis, which may be improved with receipt of intensive induction.